The Influence of Work Discipline and Work Environment on Employee Performance in the General Affairs Division of the Regional Secretariat of Tangerang City - Handayani, Devi Tri; Hasanah (GoAcademica Research & Publishing, 2024)
The purpose of this study is to examine employee performance as the dependent variable influenced by work discipline and work environment, both of which serve as independent variables. The research method used is associative with a quantitative approach. The population consists of 40 employees, resulting in a sample of 40 respondents, which indicates the use of a saturated sample. Data analysis is conducted through classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. Additionally, multiple regression and R square analyses are utilized. The results indicate a positive and significant joint influence of work discipline and work environment on performance. Furthermore, there is a positive and significant partial influence of work discipline on performance, as well as a positive and significant partial influence of work environment on performance.